Preterm birth, an unresolved issue - Belizan, Jose (2013)
Premature birth is the world's leading cause of neonatal mortality with worldwide estimates indicating 11.1% of all live births were preterm in 2010. Preterm birth rates are increasing in most countries with continual differences in survival rates amongst rich and poor countries. Preterm birth is currently an important unresolved global issue with research efforts focusing on uterine quiescence and activation, the 'omics' approaches and implementation science in order to reduce the incidence and increase survival rates of preterm babies. The journal Reproductive Health has published a supplement entitled Born Too Soon which addresses factors in the preconception and pregnancy period which may increase the risk of preterm birth and also outlines potential interventions which may reduce preterm birth rates and improve survival of preterm babies by as much as 84% annually. This is critical in order to achieve the Millennium Development Goal (MDG 4) for child survival by 2015 and beyond.